IMPACT OF WEST AFRICAN SOY LIMITED (WASIL) ON MAIZE FARMERS PRODUCTIVITY IN NORTH WESTERN, NIGERIA - Ebenehi, O.; Ibrahim, F.; Adeola, S.S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the impact of West African Soy Limited Maize Farmers Intervention Scheme on maize farmers’ productivity. The study employed farm budgeting technique Gross Margin Analysis and Net Farm Income in order to net out the impact of the programme on the maize productivity of the beneficiaries. Purposive and proportionate sampling technique was used in selecting 282 households’ heads who benefitted from the programme while another 282 non-beneficiaries’ households were randomly selected and used as control group. Data were collected through the administration of questionnaire and analyzed using descriptive and inferential statistics. the result of the socio-economic characteristics revealed that both beneficiaries and non-beneficiaries are in their active years with a mean of 40years and they are mostly married 83% and 77% for both beneficiaries and non-beneficiaries respectively. On the part of household size, the beneficiaries have a household size of an average of 9persons while the non-beneficiaries are with an average of 7 persons, for the years of experience the beneficiaries and non-beneficiaries have a mean of 12 and 13 years respectively. The results of gross margin analysis revealed that for every N1 invested in maize production by the beneficiaries and non-beneficiaries in the study areas a profit of N 9.9k/ha and N5.5k/ha is made respectively. Thus, it could be concluded that maize production for beneficiaries is more economically viable when compared with the N9.9k/ha profit made by the beneficiaries, it can be concluded that the beneficiaries make more profit from maize production in the study area than the non-beneficiaries The programme, though a private sector initiative is such that has the potential of ensuring increased income for the poor resource small holder farmers in the rural areas of North-Western, Nigeria. The study therefore recommends that female household heads need to be encouraged to key into the programe in order to improve their income base.